Pengaruh Games Online Higgs Domino terhadap Materi Sistem Hukum di Indonesia pada Mata Pelajaran PPKN di Kelas XI SMA Al Washliyah Tanjung Morawa Tahun Pembelajaran 2021-2022 - Lilis; Samsul Bahri (Education & Learning, 2023)
This study aims to determine the effect of Higgs Domino's Online Games on Legal System Materials in Indonesia in Class XI Civic Education Subjects at SMA AL-Washliyah Tanjung Morawa TP. 2021-2022. The population of this study were all class XI-1 Private High School Al-Washliyah Tanjung Morawa. The sample of this study amounted to 44 of the 130 existing population. The method used in this study is an experimental method with a research design of one group pre test and post test design. The instrument used is a multiple choice questionnaire. The average value before using the legal system method in Indonesia is 41.75 and the standard deviation is 62.36, while the average value after using the legal system method in Indonesia is 86.27 and the standard deviation is 95.70. Thus, it can be said that the test scores using the legal system method in Indonesia in PPKN subjects are higher than before using the legal system method in Indonesia in PPKN subjects. Based on the data above, it can be concluded that the legal system method in Indonesia in PPKN subjects has a positive effect on the influence of Higgs Domino Online Games on Legal System Materials in Indonesia in PPKN Subjects for Class XI SMA AL-Washliyah Tanjung Morawa TP.2021-2022.